TEACHER’S WORK VALUES: A KEY TO ENHANCING WORK ENGAGEMENT: English - Aquino, Rommel; CASTILLO, SHIELA; HONRADO, MARVIN (CV. ARGA FARMA, 2024)
The school is the cornerstone of the global education system, with educators crucial to providing high-quality education. Outstanding teacher performance leads to positive student experiences, and teacher engagement is key to stakeholder satisfaction. However, there is a gap in understanding how specific work values influence teacher engagement. This study investigates the relationship between teachers' work values and their engagement levels at the College of Business and Public Administration, Eulogio